2017
DOI: 10.1111/pce.12979
|View full text |Cite
|
Sign up to set email alerts
|

Barley transcriptome analyses upon interaction with different aphid species identify thionins contributing to resistance

Abstract: Aphids are phloem‐feeding insects that cause yield loss on a wide range of crops, including cereals such as barley. Whilst most aphid species are limited to one or few host species, some are able to reproduce on many plants belonging to different families. Interestingly, aphid probing behaviour can be observed on both host and non‐host species, indicating that interactions take place at the molecular level that may impact host range. Here, we aimed to gain insight into the interaction of barley with aphid spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…Arabidopsis (Jaouannet et al, 2015). However, in both the M. persicae-barley poor-82 host interaction and the R. padi-Arabidopsis non-host interaction probing of the leaf 83 surface takes place (Escudero-Martinez et al, 2017, Jaouannet et al, 2015. In line 84 with our previous findings, choice assays showed that both aphid species will settle 85 on and interact with non-/poor-host plant species if given a choice, with 10% of 86 aphids found on non-/poor-hosts after 24h.…”
Section: Brevicoryne Brassicae Linnaeus (Cabbage Aphid) On Host Brassmentioning
confidence: 99%
See 4 more Smart Citations
“…Arabidopsis (Jaouannet et al, 2015). However, in both the M. persicae-barley poor-82 host interaction and the R. padi-Arabidopsis non-host interaction probing of the leaf 83 surface takes place (Escudero-Martinez et al, 2017, Jaouannet et al, 2015. In line 84 with our previous findings, choice assays showed that both aphid species will settle 85 on and interact with non-/poor-host plant species if given a choice, with 10% of 86 aphids found on non-/poor-hosts after 24h.…”
Section: Brevicoryne Brassicae Linnaeus (Cabbage Aphid) On Host Brassmentioning
confidence: 99%
“…Prior to probing the leaf 15 surface aphid behaviour can be influenced by a range of these factors including leaf 16 colour, emitted volatile organic compounds and leaf surface components, such as 17 epicuticular waxes or trichomes (Doring, 2014, Doring & Chittka, 2007, Neal et al, 18 1990. Regardless of whether the aphid encounters a host or non-host plant species 19 their specialised mouthparts, known as stylets, are utilised to probe into the plant 20 tissue (Escudero-Martinez et al, 2017, Jaouannet et al, 2015, Powell et al, 2006. 21…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations